2017
DOI: 10.1016/j.aju.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar plasma kinetic enucleation of non-muscle-invasive bladder cancer: Initial experience with a novel technique

Abstract: ObjectiveTo assess the effectiveness and safety of bipolar plasma kinetic energy for en bloc enucleation of non-muscle-invasive bladder cancer (NMIBC).Patients and methodsIn all, 46 patients diagnosed with suspected NMIBC were included. All patients were diagnosed using ultrasonography, computed tomography, and diagnostic cystoscopy, and then underwent bipolar plasma kinetic enucleation of bladder tumour (PKEBT). At the end of the procedure, all patients had a single-dose (40 mg in 40 mL saline) intravesical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The high-frequency current forms an electromagnetic field through conductive normal saline, which is finally converted into macromolecules in target tissue decomposition organisms. 30 PC and PKRBT are two surgical methods that can effectively preserve the bladder function of patients while achieving radical resection of tumor tissues. This study mainly observes the clinical efficacy of these two surgical modalities in patients with BC.…”
Section: Discussionmentioning
confidence: 99%
“…The high-frequency current forms an electromagnetic field through conductive normal saline, which is finally converted into macromolecules in target tissue decomposition organisms. 30 PC and PKRBT are two surgical methods that can effectively preserve the bladder function of patients while achieving radical resection of tumor tissues. This study mainly observes the clinical efficacy of these two surgical modalities in patients with BC.…”
Section: Discussionmentioning
confidence: 99%
“…3 Over the past 2 decades, many studies have reported on the clinical utility of ERBT, and evidence is increasingly available on safety, recurrence rate, and ERBT specimen quality. 4–14,18–23…”
Section: Discussionmentioning
confidence: 99%
“…Such values made the En-bloc resection in majority of cases possible (according to the guidelines recommendations ̶ up to 3 cm). In more than 55% cases the tumor lesions were mainly located on the side walls [19]. In two studies data regarding the average resignation of the detected tumors were not presented (Table 1).…”
Section: Fig 1 Technique Of En-bloc Resection (Clinical Case) Discumentioning
confidence: 95%